Enhancing teacher development in the teaching of Agricultural Sciences at school - Solomon, Baas Nkwenyana (University of the Free State, 2018)
The study aimed at enhancing teacher development in the teaching of Agricultural Sciences at school. The need to address the aim of the study existed because the integration of the subject agricultural sciences with other subjects in the school curriculum remains a challenge for some teachers because they have not specialized in Mathematics, Physical Sciences, Life Sciences, Technology, Economics, Geography and other subjects which are needed as additional approaches to teaching and learning the subject Agricultural Sciences. This ensues in frustrations in teachers. The interest in enhancing teacher development in the specified subject was raised by the lack of teachers who specialized in teaching Agricultural Sciences at school. Some school-based departmental heads take no interest in providing school-based continuous teacher development and support since they are not employed to manage the allocated subject at school. The problem under study was enlarged by an inadequate number of subject advisors who are expected to provide continuous teacher development and support to a high number of schools that offer Agricultural Sciences. The theoretical framework used in the study was Critical theory. The study used Teacher development as a conceptual framework. Critical theory helped us to dig deeper, through questions, comments and critique, in determining further possibilities of transforming the current efforts in the Agricultural Sciences teacher development programmes. Teacher development is a process and, therefore, different training and support is needed at different stages of this continuum. The education that teachers receive has the potential to make a difference to children’s learning and therefore warrants careful attention. Participatory action research (PAR) was used for generating data that helped to achieve the aim of the study. The research question was: How can we enhance teacher development in the teaching of agricultural sciences? Three schools in the Thabo-Mofutsanyana district, the subject advisor, and the farm manager participated in the study. The study used critical discourse analysis (CDA) as a means to analyse, interpret and eventually report the data. The three levels of CDA, namely textual analysis, discourse analysis and socio-cultural analysis assisted to expose and eradicate the existence of power relations in our quest. Findings: Through the study it was found that teachers could not be assisted in creating lessons where agricultural sciences could be learned through the study of real-world issues that affect people’s health and well-being. In addition, the study found that there was a discord between the self and external and school-based teacher development initiatives for Agricultural Sciences teachers. The study also found that breeder societies, organisations of agriculture educators and AgriSETA were not engaged in enhancing teacher development as alternatives to institutions of higher learning. Subsequent to the above was the finding that teacher development programmes were not assisting teachers to link home and school ontologies in the teaching of Agricultural Sciences. Ultimately the study found that some teacher development policies seldom enhanced epistemological needs of Agricultural Sciences teachers.
Dissertation (M.Ed. (Policy Studies and Governance))--University of the Free State (Qwaqwa Campus), 2018
Keywords: Critical theory (CT); Teacher development (TD); Participatory action research (PAR); Critical discourse analysis (CDA); Clear and focused lessons; Frequent monitoring and assessment; Variety in teaching and assessment activities; Reward and incentive system; Agricultural sciences